IMPLEMENTATION OF CREATIVE LEARNING METHODS INCREASE STUDENT LEARNING MOTIVATION IN SOCIAL STUDIES SUBJECTS - Mauizatul Hasanah; Cahya Ningsih (Indonesian Journal of Education (INJOE), 2022)
The purpose of this research is to reveal about: 1) describe the preparation of teachers in implementing the creative learning method in increasing the learning motivation of fifth grade students in social studies; 2) implementing creative learning methods in increasing the learning motivation of fifth grade students in social studies; 3) describe what obstacles the teacher faces in implementing the creative learning method in increasing the learning motivation of fifth grade students in social studies subjects. This study uses a qualitative approach and descriptive research type. Data collection techniques using interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data display and conclusions. The results of this study indicate that: 1) the difficulties of Aqidah Akhlak subject teachers in assessing students' attitudes are difficulties in determining attitude instruments in attitude assessment, lack of time to assess student attitudes, and difficulty developing attitude assessment criteria; 2) the method of the Aqidah Akhlak subject teacher in assessing student attitudes consists of several ways, namely compiling types of student attitudes, observing students directly, determining attitude criteria according to student character, and increasing cooperative relationships.